2012
DOI: 10.1177/1359104512465739
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of support-seeking in young people attending a Youth Offending Team: An interpretative phenomenological analysis

Abstract: High levels of mental health problems have been identified in young people who have offended (committed/been convicted of a criminal offence). However, as with many young people, they tend not to seek support for their difficulties. This research aimed to explore support-seeking in this population by asking 'What are the perceptions of support-seeking in young people attending a Youth Offending Team?' Semi-structured interviews were carried out with six males (aged 13-18) and the transcripts were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Early experiences have indeed been found to impact social support, with reports that attachment styles are related to the availability of socially supportive relationships, social support skills (Ma, 2006), willingness to seek social support (Bartholomew et al 19997) and feelings experienced at receiving support (Sarason et al 1990). This has also been evidenced with YPwO, who have reported that a damaged self, complexity of relationships and internal conflict acted as barriers to seeking social support (King et al 2014). Figure 1.6: Integrated perspective of perceived social support and outcome (Sarason et al 1990)…”
Section: Social Support: An Integrated Perspectivementioning
confidence: 81%
See 4 more Smart Citations
“…Early experiences have indeed been found to impact social support, with reports that attachment styles are related to the availability of socially supportive relationships, social support skills (Ma, 2006), willingness to seek social support (Bartholomew et al 19997) and feelings experienced at receiving support (Sarason et al 1990). This has also been evidenced with YPwO, who have reported that a damaged self, complexity of relationships and internal conflict acted as barriers to seeking social support (King et al 2014). Figure 1.6: Integrated perspective of perceived social support and outcome (Sarason et al 1990)…”
Section: Social Support: An Integrated Perspectivementioning
confidence: 81%
“…YPwO expressed the view that barriers related to issues of understanding, stigma and confidentiality, prevent accessing support (King et al 2014;Walsh et al 2011). Sociocultural barriers to effective support are claimed to arise from the 'new youth justice system' (Goldson 2000), borne out of the Crime and Disorder Act 1998 (CDA, 1998).…”
Section: Service and Policy Context For Ypwomentioning
confidence: 99%
See 3 more Smart Citations